Tolerance and intolerance in the European reformation - Grell, Ole Peter 1950-; Scribner, Robert W. 1941-1998 (Cambridge Cambridge University Press, 1996)
This volume offers a re-interpretation of the role of tolerance and intolerance in the European Reformation. It questions the traditional notion of a progressive development towards greater religious toleration from the beginning of the sixteenth century onwards. Instead, it places incidents of religious tolerance and intolerance in their specific social and political contexts. Fifteen leading scholars offer a comprehensive interpretation of this subject, covering all the regions of Europe that were directly affected by the Reformation in the crucial period between 1500, when northern humanism had begun to make an impact, and 1648, the end of the Thirty Years War. In this way, Tolerance and Intolerance in the European Reformation provides a dramatically different view of how religious toleration and conflict developed in early modern Europe.
Introduction / Ole Peter Grell -- The travail of tolerance : containing chaos in early modern Europe / Heiko A. Oberman -- Preconditions of tolerance and intolerance in sixteenth-century Germany / Bob Scriber -- Heresy executions in Reformation Europe, 1520-1565 / William Monter -- Un roi, une loi, deux fois : parameters for the history of Catholic-Reformed co-existence in France, 1555-1685 / Philip Benedict -- Confession, conscience, and honour : the limits of magisterial tolerance in sixteenth-century Strassburg / Lorna Jane Abray -- One Reformation or many? : Protestant identities in the later Reformation in Germany / Euan Cameron -- Toleration in the early Swiss Reformation : the art and politics of Niklaus Manuel of Berne / Bruce Gordon -- Tolerance and intolerance in sixteenth-century Basle / Hans R. Guggisberg -- Exile and tolerance / Ole Peter Grell -- The politics of toleration in the Free Netherlands, 1572-1620 / Andrew Pettegree -- Archbishop Cranmer : concord and tolerance in a changing Church / Diarmaid MacCullogh
Toleration for Catholics in the Puritan revolution / Norah Carlin -- The question of tolerance in Bohemia and Moravia in the age of the Reformation / Jaroslav Pánek -- Tolerance and intolerance in sixteenth-century Hungary / Katalin Péter -- Protestant confessionalisation in the towns of Royal Prussia and the practice of religious toleration in Poland-Lithuania / Michael G. Müller
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Reformation -- Congresses; Religious Tolerance -- Europe -- History, 16th century -- Congresses; Religious Tolerance -- Europe -- History, 17th century -- Congresses; Religious Tolerance -- Europe -- History -- 17th century -- Congresses; Reformation -- Congresses; Religious Tolerance -- Europe -- History -- 16th century -- Congresses; Reformation ; Congresses; Religious tolerance ; Europe ; History ; 16th century ; Congresses; Religious tolerance ; Europe ; History ; 17th century ; Congresses